An experimental methodology for quantitative characterization of multi‐site fatigue crack nucleation in high‐strength Al alloys. Issue 6 (12th February 2016) - Jin, Y.; Cai, P.; Tian, Q. B.; Liang, C. Y.; Ke, D. J.; Wang, G.; Zhai, T.
Abstract: An experimental method was developed to quantify the multi‐site fatigue crack initiation behaviour of engineering alloys in four‐point bend fatigue testing under stress control. In this method, fatigue crack initiation sites [fatigue weak‐links (FWLs)] were measured on the sample surface at different cyclic stress levels. The FWL density in an alloy could be best described using a three‐parameter Weibull function of stress, although other types of sigmoidal functions might also be used to quantify the relation between weak‐link density and stress. The strength distribution of the FWLs was derived from the Weibull function determined by fitting the weak‐link versus stress curve experimentally obtained. As material properties, FWL density and strength distribution could be used to characterize the fatigue crack nucleation behaviour of engineering alloys quantitatively and evaluate the alloy quality in terms of weak‐link density and strength distribution. In this work, the effects of environment, types of microstructural heterogeneities and loading direction on FWLs were all studied in detail in AA7075 T651, AA2026 T3511, A713 alloys, etc. It was also found that FWL should be quantified as a Weibull‐type function of strain instead of stress, when the applied maximum cyclic stress exceeded the yield strength of the tested alloy.